Sustainable Antimicrobial Nanomaterials: A Promising Treatment for Multiple Drug Resistant Microorganisms - Raut, Neha S.; Musle, Ram; Raut, Monika; Kanchhul, Rakesh M.; Taywade, Ekant S.; Umekar, Milind J. (Indian Journal of Pharmaceutical Education and Research, 2023)
ABSTRACT: Antibacterial drugs had an essential role in the treatment of various diseases from a long-time whereas excess use leads to resistance and toxicity which is a great challenge in the health sector. The most important factors responsible for the spread of antibiotic resistance includes globalization, self-medication, repetitive and excess use of antimicrobials, continuous intake of broad-spectrum agents, and less availability of an effective antimicrobial agents. The increased resistance of antibiotic towards many microorganisms threatens further use in the treatment or the increased dose may lead to toxicity. It is also estimated and found that if no new antibiotics or antibacterial drugs discovered in the current situation then there is an urgent need to identify and develop an alternative effective method for the treatment of antibiotic resistant. Green synthesized nanoparticles are most effective, eco-friendly, and efficient on resistant microorganisms. Therefore, the present review is to summarise the mechanisms, classifications, limitations, and applications, of various nanotherapeutics nano formulations as a promising and effective treatment for the repetitive development of antibiotic resistance by different strains of bacteria.
Keywords: Nanomaterial; Antibiotic resistant; Microorganism; Metal; Antibacterial; Chemotherapy